(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The paper studies the types of lexical transformations of English political terminology in the process of its translation into Ukrainian. It deals with the aspects of translation techniques, with the pitfalls of translator’s work.